Model of Translation Textbook for Teaching English as Foreign Language (TEFL) Pedagogical Purpose - Siregar, Masitowarni (Association of Language Teachers in Southeast Asia (ALTSA), 2019)
This study was aimed at developing the model of translation textbook for teaching English as a foreign language purpose. Therefore, Research and Development (R&D) design was applied to develop the translation textbook for TEFL pedagogical purpose. Moreover, there are four steps to develop the textbook which drafting, peer review – revise, expert review – revise and final texbook. The result of study shows the while drafting the content of the textbook were 1) preface, 2) Competences, 3) Presentation and 4) Assessment. Then from the peer review, the contents of the textbook were developed to 1) overview, 2) competencies, 3) orientation, and 4) assessment. From the expert review, the content of textbook were deveoped to 1) overview, 2) competencies, 3) orientation, 4) assessment, and 5) further reading. In conclusion, this model has been developed according to peer and expert views. Therefore, this model of translation textbook is suggested to be used in English Education Program in Indonesia.